Cement Sheath Integrity in Anisotropic Shale Formations: A Numerical Investigation. (7th April 2022) - Li, Xiaorong; Zeng, Yijin; Ding, Zechen; Liu, Rengguang; Lin, Hai
Abstract : Cement sheath should provide zonal isolation and structural support during the full life cycle of a well. However, achieving long-term cement sheath integrity under complex geological and operational conditions, especially in bedding shales characterized by strong anisotropy, is still a great challenge. Thus, to better understand the effects of the anisotropy of shales on cement sheath integrity, this paper developed a 3D coupled thermal-hydro-mechanical model of the formation-cement-casing system. Stress generation and evolution within cement sheath are also considered in the modeling. The model is validated against analytical solutions and physical experimental results. Then, sensitivity analyses were performed to investigate the initial stress of cement sheath and shale anisotropy on cement sheath integrity. The results show that the anisotropy of Young's modulus has a greater influence on cement sheath integrity compared to the anisotropy of Poisson's ratio. Debonding between the cement sheath and formation can be easily generated due to the shale's high anisotropy of Young's modulus. The aperture of the microannulus along the cement interface varies with the angle between the wellbore axis and the bedding plane. The minimum microannulus is developed where the wellbore is parallel to the shale's bedding planes. The results also indicate that initial stress generated in the cement sheath after its hardening is beneficial for the integrity of the cement-formation interface.